2009
DOI: 10.1007/s11886-009-0025-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac dysfunction induced by novel targeted anticancer therapy: An emerging issue

Abstract: Increasing use of targeted anticancer agents that inhibit tyrosine kinase signaling (monoclonal antibodies or tyrosine kinase inhibitors) has dramatically improved the survival of patients with malignancies. However, cardiotoxicity, including heart failure, left ventricular dysfunction, hypertension, myocardial infarction, and thromboembolism, has occurred. Importantly, these cardiotoxicities are at least partially reversible and responsive to medical management. Early recognition of cardiovascular side effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 51 publications
(23 reference statements)
0
15
0
1
Order By: Relevance
“…Angiotensin II inhibitors, diuretics, hydropyridine calcium channel blockers (CCBs), and ␤-blockers are also possible antihypertensive agents. The nondihydropyridine CCBs (verapamil and diltizamen) are cytochrome P450 (CYP)3A4 inhibitors so are used cautiously in conjunction with VEGFIs metabolized by the CYP3A4 pathway [44,45].…”
Section: Clinical Manifestations and Managementmentioning
confidence: 99%
“…Angiotensin II inhibitors, diuretics, hydropyridine calcium channel blockers (CCBs), and ␤-blockers are also possible antihypertensive agents. The nondihydropyridine CCBs (verapamil and diltizamen) are cytochrome P450 (CYP)3A4 inhibitors so are used cautiously in conjunction with VEGFIs metabolized by the CYP3A4 pathway [44,45].…”
Section: Clinical Manifestations and Managementmentioning
confidence: 99%
“…Ela inibe duas quinases pró-apoptóticas, ASK1 e MST2 que são importantes na injúria por estresse oxidativo, gerando apoptose do miócito. A ocorrência de hipertensão pode ser atribuída à inibição dos receptores de VEGF 179 . Apesar de não ser tão comum, a cardiotoxicidade do sorafenibe pode ser grave e levar à morte.…”
Section: -Agentes Biológicosunclassified
“…Moreover, toxicities such as hypothyroidism and cardiotoxicity may have been grossly underestimated in the sunitinib registrative trial (Motzer et al, 2007) compared with the levels indicated from other recent studies of sunitinib (Rini et al, 2007;Chen, 2009;Torino et al, 2009;Di Lorenzo et al, 2009), whereas the safety profile of bevacizumab plus interferon does not seem to have changed so much over time. When considering these additional facts, the indirect economic advantage of bevacizumab plus interferon seems to be even more evident and convincing.…”
mentioning
confidence: 92%